1999
DOI: 10.1159/000028321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mannitol and Dimethylthiourea on <i>Helicobacter pylori</i>-Induced IL-8 Production in Gastric Epithelial Cells

Abstract: The present study aims at investigating the effects of mannitol and dimethylthiourea, known hydroxyl radical scavengers, on lipid peroxidation as an indicative of oxidative damage, NF-κ B activation and IL-8 production by Helicobacter pylori in gastric epithelial cells. A human gastric epithelial cell line, AGS, treated with or without mannitol and dimethylthiourea, was incubated in the absence or the presence of H. pylori. As a result, H. pylori significantly stimulated the productions of lipid peroxide and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…3 However, our previous study showed that H. pylori-induced oxygen radicals in gastric epithelial cells in the absence of inflammatory cells. 4,5 These results demonstrate the possibility that H. pylori directly turns on transcription levels of inflammatory genes in gastric epithelial cells prior to the recruitment of inflammatory cells.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…3 However, our previous study showed that H. pylori-induced oxygen radicals in gastric epithelial cells in the absence of inflammatory cells. 4,5 These results demonstrate the possibility that H. pylori directly turns on transcription levels of inflammatory genes in gastric epithelial cells prior to the recruitment of inflammatory cells.…”
mentioning
confidence: 87%
“…A ratio of bacterium/cell was adapted from previous studies. 4,5,48 Supernatants were collected for the determination of IL-8 and MCP-1 at the indicated time points. The cells were homogenized and RNA was extracted for the determination of IL-8 and MCP-1 mRNA expression.…”
Section: Cell Line and H Pylori Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interleukin-8 (IL-8), a member of the C-X-C chemokine family, is a potent chemoattractant and activator of neutrophils, monocytes, and T lymphocytes (3)(4)(5). ROS mediate the expression of IL-8 by activating oxidant-sensitive transcription factors in gastric epithelial cells (6)(7)(8).…”
mentioning
confidence: 99%